Evaluating Change Behaviour Training Model for Improving Nutrition Knowledge and Counseling Skill among Peer Couselors in Malang District - Nurul Muslihah; Intan Yusuf Habibie; Annisa Rizky Maulidana; Netty Dyah Kurniasari; Bunga Farida; Ririn Harini (Media Gizi Indonesia, 2022)
Capacity strengthening and interpersonal communication are important in social behavior change communication and would support accelerating the reduction of stunting in Indonesia. Participating actively in learning during the training model can increase capacity among the family support team and the community health workers as peer counselors. The study evaluated the changed behavior training model for nutrition knowledge and counseling skill among peer counselors. The nutrition training using active participation learning was conducted through participants' small discussions on complementary feeding problems and counseling practice. The total participation is 125 from family support teams and community health workers. The study used a mixed methodology with cross-sectional study and open interviews to explore perceived participant training on child feeding problem and couseling skills. A pre-post evaluation of nutrition knowledge showed a significant improvement score (p<0.005). At the end of the training, participants' nutrition knowledge score increased to 17 points, and the proportion of the high category of nutrition knowledge improved from 0.4% to 13.5% (p<0.005). The change behavior training model can increase counseling skills and identify barrier factors of breastfeeding and complementary feeding among peer counselors.